ANALISIS STRATEGIS MANAJEMEN MUTU DAN SUPERVISI PENDIDIKAN DALAM MENINGKATKAN STANDAR NASIONAL PENDIDIKAN DI INDONESIA - Nisriina Amiirah Faatin; Anam Sutopo; Sofyan Anif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Quality management and educational supervision are crucial instruments in ensuring the sustainability of the quality of educational output in Indonesia. This study aims to analyze the integration between the concept of Integrated Quality Management (MMT) with academic supervision practices within the framework of National Education Standards (SNP). Using descriptive qualitative methods, this study dissects various challenges in curriculum implementation, teacher pedagogical competence, and the role of the principal as a supervisor. As well as the strategic role of both aspects in making education in Indonesia more qualified and quality and supporting the achievement of effective and efficient education. The results of the study indicate that the improvement of educational quality is significantly influenced by the consistency of supervision and collaboration. As well as improving education that has good and equitable quality for students, without differentiating social status, economics, and abilities. Therefore, this study concludes that the transformation of quality management must be supported by strengthening digital literacy for educators and data-based supervision policies. In order to create a harmonious environment and have a strong character.